Resinas para facetas estéticas de próteses fixas. III. Análise conjunta das variáveis alteração dimensional e alteração de peso em função de materiais, condição de armazenamento e tempos. - Leonardi, P.; Giampaolo, E. T.; Machado Cucci, A. L. (My University, 1990)
The authors analysed the simultaneous effects of the dimensional and weight alteration of resins utilized for esthetic facets submitted to warehousing conditions and periods of time. The resins showed different behaviour and a neat correlation between dimensional alteration and weight. The condition of immersion promoted dimensional alteration 50% lower and an alteration of weight three times higher.
Resins for esthetic veneering of fixed dentures. 3. Simultaneous analysis of dimensional change variables and weight change as a function of materials, storage condition and time
Keywords: acrylic acid resin; Composite Dental Resin; polyurethan; resin; chemistry; dental care; denture; time; Acrylic Resins; Dental Veneers; Denture, Partial, Fixed; English Abstract; Esthetics, Dental; Polyurethanes; Resins, Synthetic; Time Factors